Corporate Strategy and Business Planning - Bennett Roger (M&E Pitman Publishing, 1996)
This book gives all the essential information needed to identify central issues in Strategic Management and Planning. Preface, Business Strategy, The Nature of Strategic Management, Objectives, Strategy Formulation, Forecasting, Management Audits and Environmental Analysis, Change and Chaos and the Learning Organization, Strategy and Structure, Ethical Considerations, Functional Strategies, Marketing Strategy, Financial Strategy, Human Resources Strategy, Information Technology Strategy, Manufacturing Strategy, Strategies for the Internationalization of Operations, Planning and Control, Corporate Planning, Techniques of Planning, Operational Planning, Management Control, Appendices, References and Bibliography, Examination Technique, Sample Examination Questions, Index.